Prevalence and risk factors for pterygium: a cross-sectional study in Han and Manchu ethnic populations in Hebei, China. Issue 2 (21st February 2019) - Pan, Zhouxian; Cui, Jiantao; Shan, Guangliang; Chou, Yuyu; Pan, Li; Sun, Zixi; Cui, Ze; Sun, Jixin; Cao, Yajing; Zhao, Jingjing; Ma, Xinyan; Ma, Jifei; et al.
Abstract : Aims: To investigate the prevalence, ethnic differences and associated risk factors for pterygium in Han and Manchu populations aged 40–79 years in Hebei province, China. Design: Cross-sectional study, as a part of the China National Health Survey. Setting: Hebei province, China. Participants: A multistage cluster sampling method with urbanisation level-based stratification was used to select participants for this study. A total of 4591 individuals over 40 years were recruited for this study. Inclusive criteria: (1) residents who had been living in Hebei for more than 1 year; (2) Han individuals with both parents being Han, or Manchu individuals with both parents being Manchu; (3) underwent ophthalmic examinations and (4) information in the questionnaire was complete. Main outcome measures: Multiple logistic regression analysis was used to evaluate the association between pterygium prevalence and factors of interest. Results: A total of 3790 individuals (2351 Hans and 1439 Manchus) met the study criteria, of which 248 were diagnosed with pterygium (6.5%). There was no significant difference between the prevalence rates in Hans (6.2%) and Manchus (7.2%) (p=0.232). Multivariate analysis revealed that the risk factors for grade 2 or higher pterygium were increasing age (p<0.001) and rural residence (OR 1.83; 95% CI 1.11 to 3.02; p=0.018), while the protective factors include gender (female) (OR 0.58; 95% CI 0.37 to 0.88; p=0.011), cigarette smoking (OR 0.53; 95% CI 0.34 to 0.83; p=0.005) and myopia (OR 0.50; 95% CI 0.33 to 0.77; p=0.002). Premature menopause (OR 2.66; 95% CI 1.05 to 6.72; p=0.038) increased the risk of grade 2 or higher pterygium in females, while higher high-density lipoprotein (HDL) (OR 1.94; 95% CI 1.08 to 3.47; p=0.027) was a risk factor of grade 2 or higher pterygium in males. Conclusion: The overall prevalence of pterygium in Han and Manchu population in Hebei, China was approximately 6.1%. There were no differences in the prevalence of pterygium between Hans and Manchus, and the race was not a risk factor. This is the first study to report on the positive association between premature menopause and pterygium in females and between higher HDL levels and pterygium in males.